Evaluating the Management Effectiveness of Free Nutritious Meal Program Funding: Program Managers' Perspectives at SPPG Muko Dayah - Sifa Nuzula; Zahriatul Aini (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study explores program managers' perceptions of fund management effectiveness for the Free Nutritious Meal Program (MBG) in Pidie Jaya. The findings reveal that fund management is perceived as effective, driven by a clear understanding of objectives, regulatory compliance, and functional internal oversight. Despite administrative challenges such as disbursement delays, program stability is maintained through adaptive internal coordination and field-level discretion. Theoretically, this research reinforces the Street-Level Bureaucracy framework, demonstrating that the adaptive capacity of implementers is crucial for localizing national policies. Practically, it suggests that central authorities must synchronize budget schedules with regional operational cycles to prevent liquidity constraints. These insights provide a foundation for future longitudinal studies on the maturation of new public service administrative systems.